Influence of the Boy Band BTS As Brand Ambassadors To Purchase Intention Mediated by Tokopedia 's Brand Image and Brand Awareness in Indonesia - Dian Saputri, Silvi; Vandayuli Riorini, Sri; Badzlina Nabila, Lintang (Jurnal Multidisiplin Indonesia, 2023)
BTS is currently the most famous Korean idol boy band not only in Indonesia but also throughout the world. Because of their high profits, many large companies are eyeing to work with them as Brand Ambassadors and product influencers, eventually giving rise to the term "BTS effect." This research aims to analyze the influence of Brand Ambassadors on intention to purchase skin care products which Brand Image and Brand Awareness mediate. The method used is non-probability sampling with a purposive sampling approach because the respondent is a Tokopedia user who knows Tokopedia's Brand Ambassador. Data analysis used the Statistical Package for the Social Sciences (SPSS) with 103 Tokopedia user respondents in Indonesia. The research results show that Brand Ambassadors influence Brand Image, Brand Awareness, and Purchase Intention. Brand Ambassadors have a positive influence on Brand Image and Brand Awareness.